Pengaruh Soft Skill Dan Insentif Terhadap Kinerja Sales Handphone Pt.Ziola Kolaka - Nasrah Vitria Rohmadany; Niar Astaginy (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine: (1) The effect of soft skills on the performance of PT. Ziola Kolaka's mobile phone sales. (2) The Influence of Incentives on PT. Ziola Kolaka's cellphone sales performance. This research uses a quantitative approach. Collecting data in this study using documentation and distributing questionnaires. The population of this research is all mobile phone sales who work at PT. Ziola Kolaka. While the sample of this study amounted to 30 people. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 4.0. Based on the results of the study it is known that soft skills have a positive and significant influence on mobile phone sales performance. and incentives also have a positive and significant effect on mobile phone sales performance.